Beta-aminoketones as prodrugs for selective irreversible inhibitors of type-1 methionine aminopeptidases - Altmeyer, Markus; Amtmann, Eberhard; Heyl, Carina; Marschner, Aline; Scheidig, Axel J.; Klein, Christian D. (Bioorganic & medicinal chemistry letters, 2014)
We identified and characterized β-aminoketones as prodrugs for irreversible MetAP inhibitors that are selective for the MetAP-1 subtype. β-Aminoketones with certain structural features form α,β-unsaturated ketones under physiological conditions, which bind covalently and selectively to cysteines in the S1 pocket of MetAP-1. The binding mode was confirmed by X-ray crystallography and assays with the MetAPs from Escherichia coli, Staphylococcus aureus and both human isoforms. The initially identified tetralone derivatives showed complete selectivity for E. coli MetAP versus human MetAP-1 and MetAP-2. Rational design of indanone analogs yielded compounds with selectivity for the human type-1 versus the human type-2 MetAP.
Gesehen am 26.11.2020